EKSISTENSI LEX MERCATORIA DALAM PRAKTIK KONTRAKTUAL DANPENYELESAIAN SENGKETA LINTAS NEGARA ANGGOTA PBB - Deli Bunga Saravistha (Universitas Mahendradatta, 2022)
The different legal systems of countries in the world make many international conventions available, such as UNIDROIT, UNCITRAL, CISG, COMECON, and so forth. Despite this, the conventions have not been able to fully accommodate the interests of the parties in conducting international relations. The intended international relations can be in the form of political relations and also commercial business. Many conventions at the UN, but do not necessarily require all members to follow and submit to the contents of these conventions. One of the requirements to legitimize a convention in the national domain is to ratify the convention. Then practice it in his national legal culture. Lex Mercatoria exists as a flexible international law both for adherents of the Civil Law System, Anglo Saxon and the Socialist legal system. One organization that specifically regulates world trade is the WTO or World Trade Organization, which also regulates ways of international dispute resolution. The methods practiced by the WTO were later gradually used as international customs for various countries in the world, moreover for Indonesia which officially became a member of this organization. Indonesia also hereby issues national regulations in order to adapt to international customs in the world, one of which is the issue of transnational dispute resolution. So that in this case will be further studied and analyzed regarding: a). How is the implementation of the lex mercatoria principle in carrying out international business contracts implemented in cross-country relations between UN member states? and b). What is the mechanism for resolving business disputes in the event of default or unlawful conduct across the United Nations member states?